Is council tax valuation band a predictor of mortality? - Taylor Gordon J; Beale Norman R; Straker-Cook Dawn MK (BMC, 2002)
Abstract Background All current UK indices of socio-economic status have inherent problems, especially those used to govern resource allocation to the health sphere. The search for improved markers continues: this study proposes and tests the possibility that Council Tax Valuation Band (CTVB) might match requirements. Presentation of the hypothesis To determine if there is an association between CTVB of final residence and mortality risk using the death registers of a UK general practice. Testing the hypothesis Standardised death rates and odds ratios (ORs) for groups defined by CTVB of dwelling (A - H) were calculated using one in four denominator samples from the practice lists. Analyses were repeated three times - between number of deaths and CTVB of residence of deceased 1992 - 1994 inclusive, 1995 - 1997 inc., 1998 - 2000 inc. In 856 deaths there were consistent and significant differences in death rates between CTVBs: above average for bands A and B residents; below average for other band residents. There were significantly higher ORs for A, B residents who were female and who died prematurely (before average group life expectancy). Implications of the hypothesis CTVB of final residence appears to be a proxy marker of mortality risk and could be a valuable indicator of health needs resource at household level. It is worthy of further exploration.